2016
DOI: 10.1111/jvim.14625
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Measurements in 780 Apparently Healthy Cats

Abstract: BackgroundMean systolic blood pressure in apparently healthy cats has been reported as approximately 125 mmHg using direct assessment, but there is greater variability in reported values using indirect assessment. Increasing age and the white‐coat effect are associated with increased systolic blood pressure.Hypothesis/ObjectivesTo report Doppler‐derived blood pressure measurements from a large population of apparently healthy cats and to assess epidemiologic factors associated with recorded blood pressures.Ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
55
4
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 39 publications
11
55
4
5
Order By: Relevance
“…The panel recognizes the need for breed‐specific BP ranges to be developed. In cats, no effect of breed has been observed on BP …”
Section: Normal Values For Canine and Feline Bpmentioning
confidence: 95%
See 3 more Smart Citations
“…The panel recognizes the need for breed‐specific BP ranges to be developed. In cats, no effect of breed has been observed on BP …”
Section: Normal Values For Canine and Feline Bpmentioning
confidence: 95%
“…The relationship between obesity and higher BP in dogs may be related to the prevalence of underlying disease . In cats, no effect of obesity on BP was observed by oscillometry, but cats that were underweight had slightly lower BP when measured with Doppler than those that were of ideal body weight or obese . Recent studies suggested no association among body condition score, body weight, and SBP measurements in dogs or cats, but muscle condition score and sarcopenia have been reported to affect radial but not coccygeal BP measurements in the cat …”
Section: Normal Values For Canine and Feline Bpmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is difficult to clearly classify such cases as RCM or UCM. The group of hypertensive cats included individuals with primary or secondary hypertension (4,12). Secondary hypertension was usually related to renal failure, less often to hyperthyroidism.…”
Section: Resultsmentioning
confidence: 99%